Antibody Dependent Enhancement Due to Original Antigenic Sin and the Development of SARS - Fierz, Walter; Walz, Brigitte (Frontiers in Immunology, 2020)
Human coronavirus (HCoV) is one of the most common causes of respiratory tract infections throughout the world. Two phenomena observed so far in the development of the SARS-CoV-2 pandemic deserve further attention. First, the relative absence of clinical signs of infections in children, second, the early appearance of IgG in certain patients. From the point of view of immune system physiology, such an early rise of specific IgG is expected in secondary immune responses when memory to a cross-reactive antigen is present, usually from an earlier infection with a coronavirus. It is actually typical for the immune system to respond, to what it already knows, a phenomenon that has been observed in many infections with closely related viruses and has been termed ‘original antigenic sin’. The question then arises whether such cross-reactive antibodies are protective or not against the new virus. The worst scenario would be when such cross-reactive memory antibodies to related coronaviruses would not only be non-protective but even enhance infection and the clinical course. Such a phenomenon of antibody dependent enhancement (ADE) has already been described in several viral infections. Thus, the development of IgG against SARS-CoV-2 in the course of COVID-19 might not be a simple sign of viral clearance and developing protection against the virus. On the contrary, due to cross-reaction to related coronavirus strains from earlier infections, in certain patients IgG might enhance clinical progression due to ADE. The patient’s viral history of coronavirus infection might be crucial to the development of the current infection with SARS-CoV-2. Furthermore, it poses a note of caution when treating COVID-19 patients with convalescent sera.